Life Narratives Are More Other-Centered, More Negative, and Less Coherent in Turkey Than in Germany: Comparing Provincial-Turkish, Metropolitan-Turkish, Turkish-German, and Native German Educated Young Adults - Altunnar, Neşe Hatiboğlu; Habermas, Tilmann (Frontiers in Psychology, 2018)
An individualized and coherent life story has been described as the form of identity that is required by highly mobile individualistic Western societies, whereas more family-oriented, traditional societies require more role-based, synchronic identities. Therefore entire life narratives can be expected to be more coherent and to contain more autobiographical arguments that contribute to life narrative coherence in individualistic cultures. This cultural group difference is expected to be mediated by individuals’ conformity to their respective cultural normative concept of biography. We tested these expectations by eliciting entire life narratives and cultural life scripts from students of technical universities from provincial and metropolitan Turkey, as well as from students with a Turkish migrant and a German background in urban Germany (N= 96). Expectations were confirmed for global life narrative coherence and autobiographical arguments with self-event connections. Conformity with a normative concept of biography indeed mediated cultural influences on life narrative coherence. Life narratives from Turkey also contained more family-related events and, unexpectedly, were more negative. Thus creating a coherent life narrative is more typical for cultures that require autonomous, individualized selves rather than for cultures requiring more related selves, reflecting the life story’s suitability for expressing individualized identities and its lesser suitability for expressing interdependent identities.